The Meaning Of The Lotus’s Symbol In Bubbhist Philosophy For VietNam Now - Anh, Dr. Pham Phuong; Tin, Nguyen Thien (The journal of contemporary issues in business and government, 2021)
Among the great civilizations in the world, it is impossible not to mention India, one of the cradles of Eastern civilization, the paradise land of many religious philosophyschools. This is the place where a transcendent human being, a great spiritual leader of mankind, was born Siddhattha Gotama - Shakyamuni Buddha, the founder of the Buddhist philosophical. The humanistic ideas of Buddhism have always had a positive value on human life until now. The symbol “Lotus” is not only an auspicious image but also represents the moral and human philosophies of Buddhism and the meaning of the Lotus which is valuable to Vietnamese society in contributing to building the solidarity, mutual love - the beauty of modern Vietnamese people and moral education for people according to the motto of living a good life and promoting social progress.